Monetary Policy in Central and Eastern Europe : Lessons After Half a Decade of Transition - Begg, David (IMF Working Papers; Working Paper ;, 1996)
The paper uses data from transition economies in Central and Eastern Europe to assess four questions: (i) Did the standard blueprint for stabilization work, and was it implemented? (ii) To what extent was normal macroeconomics impeded by solvency problems in banks, and how successful have been policies to improve incentives within banks? (iii) Could financial markets and other infrastructure for monetary policy have been developed more quickly? (iv) How should transition economies respond to the monetary inflows that typically accompany success? The paper concludes by evaluating the changing advice offered by external agencies during the 1990s.